INFOLOGICAL MODEL OF REHABILITATION-RESTORATION PROCESS OF PATIENTS WITH LOCOMOTIVE SYSTEM PATHOLOGY AND OPERATING RISKS - Azarhov, O. Yu. (Medical Informatics and Engineering, 2012)
In the article the modern conception of process of rehabilitation-restoration cure of patients with violations of locomotive system is represented as a five-level informative-logical model taking into account the endogenous and exogenous risks, that allows optimizing functional and social patients’ readaptation.